Incidence of chromosomal anomalies in fetuses with isolated right aortic arch: A meta‐analysis. (19th December 2019) - Luo, Qingyi; Chen, Jian; Zhang, Yu; Li, Jianhua; Su, Xuan; Wang, Qinghui; Ding, Yunchuan
Abstract: Objective: Right aortic arch (RAA) can be associated with chromosomal anomalies. However, the incidence of chromosomal anomalies when RAA is isolated (iRAA), ie, not associated with intracardiac anomalies, varies between different studies (0%‐28.5%). We have performed a meta‐analysis to allow a more accurate prenatal counselling. Methods: We searched PubMed, Embase, and Web of Science for articles related to chromosomal anomalies among iRAA fetuses until April 2019. A total of 22 relevant studies, including 670 fetuses, were selected in the final meta‐analysis. Results: The results revealed that the overall rates of chromosomal anomalies and 22q11.2 deletion in iRAA fetuses were 7.5% (95% confidence interval [CI], 4.7%‐10.8%) and 4.3% (95% CI, 2.6%‐6.4%), respectively, while the rates were lower in iRAA without extracardiac anomalies, 4.7% (95% CI, 1.1%‐10.8%) and 2.4% (95% CI, 0.5%‐5.7%). The rate of chromosomal or copy number variants including 22q11.2 deletion identified by chromosomal microarray analysis (CMA) in iRAA fetuses was 8.2% (95% CI, 5.0%‐12.1%) and 3.7% (95% CI, 1.7%‐6.6%), respectively, compared with 5.1% (95% CI, 2.5%‐8.4%) and 2.4% (95% CI, 0.7%‐5.1%) identified by traditional karyotyping. Conclusions: A considerable proportion of iRAA cases have associated chromosomal anomalies and prevalence of associated 22q11.2 deletion, and CMA is recommended if invasive prenatal testing is performed.